2003
DOI: 10.1046/j.1523-5378.2003.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Cladosiphon Fucoidan Against Helicobacter pylori Infection in Mongolian gerbils

Abstract: Cladosiphon fucoidan may deserve particular attention as a safe agent that can prevent H. pylori infection and reduce the risk of associated gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 23 publications
0
75
0
1
Order By: Relevance
“…Goni et al (2001) suggested that algal fibres such as fucoidans were resistant to bacterial metabolism. Fucoidans from different species of brown algae have been shown to inhibit the attachment of certain bacterial species in the porcine gastro-intestinal tract as well as preventing the binding of enterococci and streptococci species to the extracellular matrix proteins of animal cells (Shibata et al, 2003), indicating that the fucoidans may be acting as a powerful antimicrobial in reducing the microbial population. Secondly, the non-selective reduction in the microbial populations may be due to the agglutination properties of the extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goni et al (2001) suggested that algal fibres such as fucoidans were resistant to bacterial metabolism. Fucoidans from different species of brown algae have been shown to inhibit the attachment of certain bacterial species in the porcine gastro-intestinal tract as well as preventing the binding of enterococci and streptococci species to the extracellular matrix proteins of animal cells (Shibata et al, 2003), indicating that the fucoidans may be acting as a powerful antimicrobial in reducing the microbial population. Secondly, the non-selective reduction in the microbial populations may be due to the agglutination properties of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…They are known to have antibacterial properties as they have been shown to have the ability to inhibit the attachment of certain bacterial species to porcine gastric mucin in vitro (Shibata et al, 2003) as well as having antiviral and anti-inflammatory properties (Marais and Joseleau, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidans, the family of sulphated heteropolysaccharides, are composed mainly of a-(1-3) linked L-fucose resides (Percival and McDowell, 1967;Gahan et al, 2009). They are known to have antibacterial properties as they have the ability to inhibit the attachment of certain bacterial species to porcine gastric mucin in vitro (Shibata et al, 2003), as well as having antiviral and anti-inflammatory properties (Marais and Joseleau, 2001;Reilly et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Goñ i et al (2001) suggested that certain algal fibres such as fucoidans were resistant to bacterial metabolism. Fucoidans from different species of brown algae inhibit the attachment of certain bacterial species in the porcine GIT, as well as preventing the binding of enterococci and streptococci species to the extracellular matrix proteins of animal cells (Shibata et al, 2003). This indicates that a component of the LH b-glucan behaves as a greater antimicrobial agent than LD b-glucan.…”
mentioning
confidence: 99%
“…Many medicinal plants have long been applied as remedies to cure such diseases. Euphorbia decipiens (Ahmad et al, 2003) and sulfated polysaccharide of brown seaweed are examples of natural substances reported to have urease inhibition activity (Limuro and Wakabayashi, 2003). The data on enzyme inhibitory activity clearly show the potential of S. pecten-veneris as an active inhibitor of urease and hence suggest that it could be effective in the treatment of gastrointestinal disorders.…”
Section: Enzyme Inhibitionmentioning
confidence: 98%